Estimation of core loss in transformer by using finite element method - Muhammad Qusyairi, Abdul Nasib (2012)
Transformer is one of the important device that always been used in industry. Some of the weakness of using transformer is cost by some losses in core. By solving this problem, it can save more energy usage. To calculate the losses in traditional techniques, it can use nonlinear programming, numerical method and others. Other than that, Finite Element Method (FEM) can be used. It can predict the period for transformer; calculate core losses, flux distribution and others. In this project, FEM technique is applied to calculate the flux and loss distributions in single phase transformer using MATLAB software. This also presented the localized flux density and loss over a core. As the result, the software must be agreed with the experimental data.